Formation of the Theological Discipline “Canon Law” in the Russian Orthodox Church in the 19th Century - Priest Vladislav V. Bagan (Вестник Екатеринбургской духовной семинарии, 2022)
The article presents a retrospective look at the phenomenon of teaching and studying the theological discipline “Canon Law” in the Russian Orthodox Church in the 19th century. The work demonstrates the evolution of methods and approaches within the “Canon Law” in the specified period. The history of the scientific discipline of “Canon Law” can be divided into several stages, stretched throughout the 19th century. The initial stage of development of “Canon Law” as a theological discipline in the Russian Empire falls on the early 19th century. At this time, “Canon Law” develops as an academic discipline and integral part of the body of theological sciences. The article describes institutional changes in the field of higher theological education related to the teaching of the theological discipline of “Canon Law”. At this stage of the development of the science, monographs and textbooks on “Canon Law” were created by professors of theology and representatives of the clergy. As a theological discipline, “Canon Law” was considered to be derived from the Christian doctrine, dogmatic theology. Only later did “Canon Law” become the object of scientific research by secular lawyers and jurists. The initial period of the formation of the theological discipline of “Canon Law” is characterized by studying the field of sources of the church law. Also, this period was characterized by the first attempts to build a system of “Canon Law”, to identify the methodology of this theological discipline. The theological direction of the academic discipline “Canon Law” assumed that the central topic would be the problems of the legal status of the Church, its relations with the state, society, and social institutions. Representatives of the theological direction of “Canon Law” considered the theological problems embodied in the format of laws to be central (that implied an emergence of the popular term in the 19th century — “Church Jurisprudence”). In conclusion, the article presents the complexity and relevance of this issue in the present study of Canon Law. The author traces the changes in thematic priorities and leading areas of research in the development of Canon Law as a theological discipline throughout the 19th century.